ROLE OF MEDIA FOR SPORT AND HEALTH: CONTEMPORARY ANALYSIS - Perdana, Satya; Sumaryanto, Sumaryanto; sumarjo, sumarjo; Saputra, Danny Eka Wahyu; Subekti, Heru; Abrori, Rifki (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
AbstractThis research focuses on the role of media from conventional to digital in sports and health. Data analysis in this research used descriptive qualitative method, involving literature study, documentation, and observation of media in society curently. The research study includes media users and parties involved in the fields of sports and health. Samples were selected purposively to produce data that reflects the diverse characteristics of Indonesian society regarding the use and utilization of information media. This research shows that the media plays significant role in shaping the way people think and act toward sports and health. Media not only provides information but is also an essential carrier in inspiring, educating, and motivating people to live healthy lives. This research contributes for increasing understanding of how media, both conventional and digital, can be the agent of change in promoting, supporting, and socializing sport and healthy lifestyles in Indonesia. The research conclusion emphasizes the importance of the increasingly varied growing and even integrated role of the media in providing sport and health information to the public. Media literacy, intermedia collaboration, and the use of social media in the context of sports and health promotion are increasingly considered as an essential means in current society.Keywords: role, media, sports, health